Gray matter alterations in early aging: A diffusion magnetic resonance imaging study. Issue 8 (31st December 2013) - Rathi, Y.; Pasternak, O.; Savadjiev, P.; Michailovich, O.; Bouix, S.; Kubicki, M.; Westin, C.‐F.; Makris, N.; Shenton, M.E.
Abstract: Many studies have observed altered neurofunctional and structural organization in the aging brain. These observations from functional neuroimaging studies show a shift in brain activity from the posterior to the anterior regions with aging (PASA model), as well as a decrease in cortical thickness, which is more pronounced in the frontal lobe followed by the parietal, occipital, and temporal lobes (retrogenesis model). However, very little work has been done using diffusion MRI (dMRI) with respect to examining the structural tissue alterations underlying these neurofunctional changes in the gray matter. Thus, for the first time, we propose to examine gray matter changes using diffusion MRI in the context of aging. In this work, we propose a novel dMRI based measure of gray matter "heterogeneity" that elucidates these functional and structural models (PASA and retrogenesis) of aging from the viewpoint of diffusion MRI. In a cohort of 85 subjects (all males, ages 15–55 years), we show very high correlation between age and "heterogeneity" (a measure of structural layout of tissue in a region‐of‐interest) in specific brain regions. We examine gray matter alterations by grouping brain regions into anatomical lobes as well as functional zones. Our findings from dMRI data connects the functional and structural domains and confirms the "retrogenesis" hypothesis of gray matter alterations while lending support to the neurofunctional PASA model of aging in addition to showing the preservation of paralimbic areas during healthy aging. Hum Brain Mapp 35:3841–3856, 2014 . © 2013 Wiley Periodicals, Inc.